Project Communication And Project Performance: Case Of Software Development In Manufacturing Environment - Gan, Tan Chen Rong (2018)
Communication is an important life skill that allow team members to have better understanding and to connect team. The role of project manager is to ensure that everyone associated with the project has a common set of expectation of what is to be delivered, when and at what cost. Due to ineffective communication among team members or within user, it leads to high percentage of project failure. Hence, the purpose of this research is to investigate the key success factors in communication for software development project. In addition, the study of the impact of success factor in communication on software project performance had been investigated.